Comparison between translucencies of anterior resin composites and natural dental tissues. Issue 3 (26th February 2021) - Balci, Melin; Ergucu, Zeynep; Çelik, Esra Uzer; Turkun, Lezize Sebnem
Abstract: We aimed to assess the translucencies of seven anterior resin composites in comparison to natural dental tissues under dry and hydrated conditions. Seven resin composites—Clearfil Majesty ES‐2 (A1‐AE1), Essentia (LE‐Universal), Ceram‐X Duo (E1), Synergy D6 Enamel (Universal White Opaque), Harmonize (A1), Filtek Ultimate (XW Enamel), and Zenit (W2)—were used. Five disc‐shaped (5 × 1 mm) specimens of each shade were fabricated, and enamel and dentin slices were obtained from extracted teeth. The color coordinates of dry and hydrated samples were measured using the SpectroShade Micro device. Translucency parameter (TP) values were calculated using a formula derivated from the Commission Internationale de l'Eclairage coordinates. Two‐way analysis of variance (ANOVA) was used to assess the interaction between the substrate and the storage medium. One‐way ANOVA and Tukey tests were used to compare the TP values, and the t test was used to compare the translucency parameter values of dry and hydrated samples ( P  < .05). Translucency parameter values of all dry and hydrated resin composites were higher than those of enamel and dentin samples ( P  < .05) except for Clearfil Majesty ES‐2 A1 and Ceram‐X Duo E1. Hydration increased the translucency parameter value of all samples ( P  < .05) except Ceram‐X Duo E1, Harmonize A1, and Filtek Ultimate XW shades where the values were unchanged. Translucency seems to be material‐specific, and no generalization relating to the different substance classes could be made. Hydration and type of materials had a significant effect on TP values. Furthermore, translucency parameter values of anterior resin composites were higher than those of dental tissues, different from each other, and increasing or remain unchanged with hydration depending on the brands tested.